Update on photoprotection - Reena Rai; Sekar C Shanmuga; C R Srinivas (Wolters Kluwer Medknow Publications, 2012)
Photoprotection by sunscreens, clothing and glasses are important to protect the skin against the detrimental effects of sun exposure. In order to achieve complete protection, topical strategies must shield against the range of solar wavelengths ultraviolet A, ultraviolet B, infrared radiation that can damage the skin. To provide the necessary broad spectrum coverage, combinations of chemical and physical UV filters along with molecules that are capable of interfering with and/or preventing the deleterious effects of sunlight are discussed in this review.